Model penataan desa kerajinan kayu di Junrejo Kota Batu - A. Tutut Subadyo (Jurnal Penelitian, 2003)
The development of handicraft industrial villages is a strategic effort that is beneficial for increasing production and has broad implications for rural social, economic and physical development. This effort is carried out through a regional spatial planning model as an effort to realize the idea of the "one village one product" program. The spatial planning of the Junrejo Village area, will have an impact not only on the development of handicraft production but will broadly affect the economic development of the village, the physical environment of the village as an industrial center, and can also be directed as a village supporting tourism programs because of its strategic location on the Malang-Batu tourist route. Based on the results of the analysis, the synthesis of the spatial planning model of Junrejo Wood Craft Village, Batu City, has the opportunity to be developed better where the facilities and infrastructure for its development are relatively adequate.